Factual beliefs and credibility according to the Spinozian model - Rivas Tinoco, Marlon Paul (2022)
Most people have claimed that religious beliefs are constituted in the same way as factual beliefs. Eric Mandelbaum suggests a more radical view, for he claims that forming a belief, whether it is religious credence or genuine belief, is similar to having direct contact with a fact that is perceived or represented in our minds: the fixation of beliefs is an effortless and automatic process. This model of our mind’s architecture is called “the Spinozan model”. Neil Van Leeuwen, on the contrary, claims that factual beliefs characterize the background and default frame that we use for tracking truths and behaving in determined ways, whereas religious beliefs function differently. This paper aims to show that, even though Van Leeuwen’s distinction between factual beliefs and religious credences is more plausible than the Spinozan model’s presupposition that both attitudes are the same kind of attitude, the Spinozan model could still be introduced as a feature for each of those kinds.